2005
DOI: 10.1530/eje.1.01987
|View full text |Cite
|
Sign up to set email alerts
|

Different expression of catecholamine transporters in phaeochromocytomas from patients with von Hippel-Lindau syndrome and multiple endocrine neoplasia type 2

Abstract: The findings show that, in addition to differences in catecholamine biosynthesis, phaeochromocytomas in MEN 2 and VHL syndrome also differ in expression of the transporters responsible for uptake and vesicular storage of catecholamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 27 publications
12
35
0
Order By: Relevance
“…Saveanu et al (37) observed a lower NET messenger RNA expression in VHL-related PPGLs than sporadic PPGLs, whereas expression of NET in RET-related PPGLs was higher. We observed a cytoplasmic staining for NET and VMAT-1 as previously reported by Huyhn et al (36). Our study confirms genotype-dependent differences in the expression of NET and VMAT-1.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Saveanu et al (37) observed a lower NET messenger RNA expression in VHL-related PPGLs than sporadic PPGLs, whereas expression of NET in RET-related PPGLs was higher. We observed a cytoplasmic staining for NET and VMAT-1 as previously reported by Huyhn et al (36). Our study confirms genotype-dependent differences in the expression of NET and VMAT-1.…”
Section: Discussionsupporting
confidence: 92%
“…Differences in the expression of catecholamine transporters have been reported between RET-and VHL-related tumors (36,37). Huyhn et al (36) showed that RET-related PPGLs expressed more NET messenger RNA and protein than VHL-related tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted from frozen phaeochromocytoma tumour samples and reverse transcribed as previously described (Huynh et al 2005). Quantitative PCR was performed with an ABI 7000 Sequence Detector (Applied Biosystems, Foster City, CA, USA) using PCR conditions consisting of 40 cycles of 15 s at 95 8C and 1 min at 60 8C.…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…Another important catecholeamine transporter in noradrenaline-producing chromaffin cells or neurons is SLC18A1 (also called VMAT1; vesicular monoamine transporter 1). The differential expression levels of its transcript have been discussed in previous studies concerning neuroblastoma (33), phaeochromocytoma (34,35), as well as in gastrointestinal endocrine tumors (36). In a recent study, Revet and colleagues showed a connection of the Phox2-pathway to the Delta-Notch pathway via the homeobox transcription factor MSX1 (37).…”
Section: Discussionmentioning
confidence: 99%